PENGARUH DEBT DEFAULT, DISCLOSURE, OPINI AUDIT TAHUN SEBELUMNYA, UKURAN PERUSAHAAN, DAN OPINION SHOPPING TERHADAP PENERIMAAN OPINI AUDIT GOING CONCERN - Randy Harris; Wahyu Meiranto (Diponegoro Journal of Accounting, 2015)
Nowadays, the task of auditors increasingly widespread, not only accountable to disclose financial information, but also information that is not limited in the things revealed in the financial statements, such as disclosure of information about the existence and continuity of corporate entities. Auditors are expected to not only check the financial statements, but also can make predictions and assess the entity's ability to maintain the continuity of their business enterprise. The purpose of this study was to examine the influence of debt default, disclosure, audit opinion in the previous year, the size of the company, and the opinion shopping to going concern audit opinion. The sample used in this study are manufacturing companies listed in Indonesia Stock Exchange in 2009-2013. This study population as much as 130 samples included 24 selected by purposive sampling method companies with the observation period of 5 (five) years. Data were analyzed using logistic regression analysis model. The results of this study indicate that debt default, disclosure, audit opinion of the previous year and opinion shopping significantly influence the going-concern audit opinion. The size of the company did not have significant effect on the going concern audit opinion.